Kajian tentang karakter berbasis nilai-nilai kearifan lokal pada masyarakat adat Kampung Kuta Kecamatan Tambaksari Kabupaten Ciamis - Sukmayadi, Trisna (Jurnal Civics: Media Kajian Kewarganegaraan, 2016)
This study was aimed at exploring the values of local wisdom of the indigenous peoples whose existence is still kept below the brunt of globalization and modernization so strong. This is a case study. Its results indicate: (1) the indigenous peoples perceived that local knowledge is a cultural heritage as a noble value, handed down by ancestors as identity formation and identity that must be maintained and preserved. Characters that are inherited are soft, regular, efficiency, discipline, shared caring, teach each other, sincere, obedient /submissive, visionary (thinking ahead), responsible, dedicated, loyal, sympathy, empathy, compassion, tolerancesense, willing to sacrifice, faith and piety, simple, cherish health, thoughtful, and constructive thinking, which are reflected in the art, proverbs,  and way of life; (2) the inheritance of the character value is done by oral traditions and examples directly transmitted through traditional ceremonies; (3) The persistence reinforcing factor of the values of local wisdom, is the fact that "pamali" (meaning prohobition), is still held firmly by community.